2013
DOI: 10.1016/j.bcmd.2012.10.002
|View full text |Cite|
|
Sign up to set email alerts
|

Ablation of the Kell/Xk complex alters erythrocyte divalent cation homeostasis

Abstract: XK is a putative transporter of unknown function that is ubiquitously expressed and linked through disulfide bonds to Kell protein, an endothelin-3 (ET-3)-converting enzyme. We generated three knockout (KO) mice that lacked either Xk, Kell or both proteins and characterized erythrocyte cation levels, transport and hematological parameters. Absence of Xk or Kell was accompanied by changes in erythrocyte K+, Mg2+, Na+ and Ca2+ transport that were associated with changes in mean cellular volume and corpuscular he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Rivera et al (47) recently reported that XK (Xkr1) regulates cell volume by transporting divalent cations. Of the 10-member TMEM16 family, five members function as Ca 2ϩ -dependent phospholipid scramblases, whereas two members carry Cl Ϫ channel activity (12,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Rivera et al (47) recently reported that XK (Xkr1) regulates cell volume by transporting divalent cations. Of the 10-member TMEM16 family, five members function as Ca 2ϩ -dependent phospholipid scramblases, whereas two members carry Cl Ϫ channel activity (12,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Kell protein shares a consensus sequence with the large family of zinc endopeptidases and has endothelin-3 converting enzyme activity of type II membrane glycoproteins. Gene disruption in mice provided evidence that cellular divalent cation regulation is functionally coupled to the Kell/XK system in erythrocytes and loss of this complex might contribute to the acanthocytosis seen in McLeod syndrome (Rivera , et al 2013). A rare phenotype termed Kell null (Ko) is characterized by the absence of Kell protein and Kell antigens from the red cell membrane and diminished amounts of XK protein (Khamlichi , et al 1995, Redman , et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In the RBC membrane, XK exists as heterodimer together with the membrane Kell protein explaining the weakened expression of all Kell antigens in Kx-deficient individuals. [13][14][15] Today, the pathophysiologic link between Kx negativity and the onset of MLS is still unclear 1 although Rivera and colleagues 16 showed that deficiency of XK and XK/Kell proteins led to altered transmembrane transport of divalent cations. 17 Absent Kx RBC antigen is pathognomonic for patients with MLS and therefore represents the diagnostic marker of highest specificity.…”
Section: Resultsmentioning
confidence: 99%